Multiplicadores reflexivos: Uma experiância do Instituto Familiae junto ao Grupo de Assistância em Transtornos Alimentares (GRATA) do HC-FMRP-USP - César, Adriana B.C.; De Pereira, Marília F.; Russo, Rosângela; Soares, Ana C.N. [UNESP]; Vicente, Azair T. (My University, 2006)
This article describes the Reflecting Practitioners Program developed by Instituto Familiae at GRATA (Grupo de Assistência em Transtornos Alimentares) placed at the Clinical Hospital of the Faculty of Medicine of Ribeirão Preto - University of Sao Paulo (HC-FMRP-USP). The aim of this program was to take care of the caretakers - the GRATA interdisciplinary team - through the development of their reflecting ability, the appropriation of their own resources and the support on constructing alternative histories and on solving situations defined by them as problematic. Thirteen monthly meeting had been carried out among Familiae members and GRATA interdisciplinary team. The changes described by the participants had occurred through sessions developed with interdisciplinary pairs and through the development of their capacity to construct more comfortable positions - as members of the team and in the relationship among professional/client/ family. This triad became to be seen by the team through its resources and abilities, instead of its flaws and lacks. As a result, horizontal relationships could be privileged instead of hierarchical ones.
Reflecting practitioners program: An experience of together institute familiae to the Grupo de Assisténcia em Transtornos Alimentares (GRATA) of HC-FMRP-USP
Keywords: Interdisciplinary Team; Reflecting Practitioners; conference paper; doctor patient relation; gastrointestinal disease; health care organization; health practitioner; health program; human; medical education; medical practice; professional competence